Mapping and monitoring the environmental impacts of mining using hyperspectral data - Ong, Cindy Chin Hui (Curtin University, 2014)
The use of multi-temporal remotely-sensed airborne hyperspectral data for monitoring environmental conditions associated with mining activities is in its infancy and few publications provide the necessary workflow and guidelines to generate validated information. This thesis provides the environmental professional with quantitative tools to make informed management decisions.Two case studies were generated to demonstrate the application of hyperspectral data for two of the mining industry’s largest challenges, namely, dust contamination and acid drainage.